Data science's cultural construction: qualitative ideas for quantitative work - Brandt, Philipp (Frontiers in Big Data, 2024)
Data scientists" have become ubiquitous, often infamously so, but they still struggle with the ambiguity of their novel role. This article studies data science's collective definition on Twitter. It adopts a cultural perspective in comparing datasets ranging from 1,025 to 752,815 tweets that respond to the challenges of studying an emergent case with unclear boundaries and substance. It brings together relations between accounts that tweeted about data science, the hashtags they used, indicating purposes, and the topics they discussed. Amid familiar commercial and technical motives, the results reveal concerns with new practical and ethical standards as a distinctive motive for constructing data science. For data scientists, the results offer a guide for positioning themselves visà-vis others and for their professional future, a sensibility for cultural dimensions in usually abstract datasets, and a heuristic for navigating increasingly abundant datasets toward surprising insights.